Factors Affecting the Performance of Village Government and Its Implications on Village Community Trust (Study in Villages in Batang Hari Regency) - Yuliana, Desi; Afrizal; Putra, Wirmie Eka (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
This study aims to examine the influence of accountability, transparency, and budget participation on village community trust through village government performance as an intervening variable. This research was conducted using a survey method by distributing questionnaires to the Village Consultative Body (BPD) in Batang Hari Regency. The sampling technique used was saturated/census sampling, which included all villages in Batang Hari Regency, totaling 110 villages. Data analysis was conducted using the Partial Least Square (PLS) approach. The research results show that directly, accountability, transparency, and budget participation influence the performance of village government, transparency, budget participation, and village government performance influence the trust of the village community, but accountability does not influence the trust of the village community. The research results indirectly show that accountability, transparency, and budget participation influence the trust of the village community through the performance of the village government as a mediator. The results of this research provide important practical implications for village governments to improve their performance.